Change of Toxic Properties of the Methotrexate when Exposed to Extreme Temperatures During Development of Drosophila melanogaster - O. N. Antosyuk; K. T. Paydiyeva (Антибиотики и Химиотерапия, 2020)
The results of the experiments show that a nutrient medium with the methotrexate has influence both on generative and on somatic cells of drosophila, depending on the concentration of this drug in a medium. Moreover, the higher temperature during development of drosophila can increase toxic properties of a methotrexate, which was observed based on an analysis of fertility of the flies developing in the environment with addition of a methotrexate, but no negative cumulative effect of cytostatic and elevated temperature were found in relation to lethality rate of the offspring. A negative effect on viability indicators was also not registered with the combined effects of the cytostatic and low temperature.